IL5 rs2069812 and IL13 rs1800925 Genetic variants as key determinants of clinically relevant asthma phenotypes - Pattara Kanoksing; Apichaya Puangpetch; Theerasuk Kawamatawong; Thatchathum Kuttiyod; Kantapat Simmalee; Roger Frutos; Putthapoom Lumjiaktase (PLoS ONE, 2026)
Type 2-high airway inflammation in adults with asthma is heavily driven by the cytokines interleukin (IL)-4, IL-5, and IL-13. While genetic variations in these cytokines are known to influence asthma pathogenesis, their specific impacts on clinically relevant phenotypes remain to be fully elucidated. This study aimed to investigate the associations between inflammatory cytokine gene polymorphisms, clinical asthma phenotypes, inflammation cell subtypes, and lung function . A cross-sectional study was conducted involving 125 adults with asthma. Genotyping was performed for the following single-nucleotide polymorphisms (SNPs): IL33 (rs1342326, rs3939286), IL4 (rs2243250, rs2243248), IL5 rs2069812, and IL13 (rs20541, rs1800925). Clinical evaluations included lung function, blood eosinophils, type 2 innate lymphoid cells (ILC2s), Th2 cells, cytokine levels, and specific IgE. The IL4 rs2243248 TT genotype was associated with higher TNF-α ( p = 0.038), while the IL13 rs1800925 polymorphism was associated with increased Th2 cell counts ( p = 0.025). Notably, IL5 rs2069812 was strongly associated with blood eosinophilia ( p < 0.001) and reduced lung function. Linear regression revealed a significant gene-dose effect of IL-5 rs2069812 T allele, which correlated with an increase in log 10 eosinophils ( β = 0.207, p < 0.001) and a decrease in post-bronchodilator FEV1% ( β = −7.38, p = 0.014). Furthermore, the IL5 rs2069812 and IL13 rs1800925 variants significantly increased the risk of blood eosinophilia (Prevalence Ratio [PR] = 2.59, p < 0.001) and fixed airflow obstruction (PR = 1.81, p = 0.039), respectively. The IL5 rs2069812 and IL13 rs1800925 polymorphisms serve as key genetic determinants of persistent blood eosinophilia and fixed airflow obstruction, respectively. Both variants significantly contribute to the severity of airflow limitation in adult asthma, highlighting their potential as biomarkers for precision phenotyping.